Access to Ecological Justice for the Marginalised People of Indonesia: Is It a Genuine or Pseudo Recognition and Protection? - I Nyoman, Nurjaya; Safaat, Rachmad (UI Scholars Hub, 2016)
The era following the 1972 Stockholm Declaration and subsequently the 1992 Rio de Janeiro Declaration, brought about a great amount of concern of the international community, in developed as well as under-developed countries, for human environment and natural resources preservation, management and protection. It includes the equitable allocation and distribution of natural resources as well as fair participation in environmental decision-making, respect and recognition of rights of the people and particularly indigenous communities. This is the so called access to justice for all that refers to a genuine access by people and communities to obtain just and fair democratic mechanism in respect and recognition of their basic legal rights in controlling and utilizing natural environment and resources for survival. Furthermore, access to justice means strengthening the fair involvement of the people with respect to preserving and managing the natural environment for sustainable development as to fulfill human rights as reflected in the State’s Constitution and legislation. In the context of Indonesia, the above mentioned rights of the people and communities to ecological justice are clearly articulated in the 1945 Constitution. The paper attempts to convey a critical analysis as to whether the 1945 Constitution provides a genuine or pseudo respect and recognition in relation to access to ecological justice of the people and particularly for marginalized people, namely indigenous people (masyarakat adat) in the multicultural state of Indonesia.